The concept of total defense in the deterrence strategy of the Republic of Serbia - Milkovski Vangel; Božić Sandra (Srpska Politička Misao)
The subject of this article refers to the examination of the convenience of the concept of total defense as a basis for designing a defense system in the function of strategic deterrence of the Republic of Serbia. The existing defense system was supposed to be based on the concept of total defense, which has not been defined, verified and generally accepted since the Republic of Serbia was founded. In accordance with the above, the question arises: whether the existing way of organizing and functioning of the defense system corresponds to the requirements of strategic deterrence. The starting point in this paper is the position that the defense system, without a previously defined and generally accepted concept of total defense, may not be fully efficient and effective in creating a credible and persuasive threat in the function of strategic deterrence. The results of the research indicate that in order to develop the necessary defenece forces capabilities and their use for strategic deterrence, it is necessary to first develop the concept of total defense. Through the development process, it is possible to achieve full agreement of all forces on their tasks, methods of engagement and associated risks. Also, with the concept of total defense, it is possible to determine measures and recommendations on changes in the existing defense system that should increase the effectiveness and efficiency of strategic deterrence. The theoretical-methodological approach used a theoretical analysis and comparison of total defense concepts in different historical and geopolitical conditions, as well as a method concept development that can meet the requirements of strategic deterrence in the conditions of a modern multidimensional strategic environment.